Demarcating transdisciplinary research in sustainability science—Five clusters of research modes based on evidence from 59 research projects. (20th December 2021) - Jahn, Stephanie; Newig, Jens; Lang, Daniel J.; Kahle, Judith; Bergmann, Matthias
Abstract: The discourse revolving around "new modes of knowledge production"—particularly in sustainability‐oriented research—seems to suggest a duality of transdisciplinary versus non‐transdisciplinary research. Yet, in reality, a spectrum of transdisciplinary research modes may be expected. This article offers an empirically grounded distinction of five research modes, based on a cluster analysis of 59 completed sustainability‐oriented research projects. Projects in one cluster approximate a transdisciplinary ideal type, while another cluster combines almost purely practice‐oriented projects. Among the three remaining clusters with varying degrees of practitioner interaction, one cluster assembles projects with strictly academic research, while realizing substantial societal impact. Furthermore, our analyses indicate that the choice of research mode strongly depends on the funding context, with mission‐oriented funding encouraging more collaborative modes. Overall, clusters with more practitioner interaction display stronger societal outputs and impacts at the cost of academic outputs and impacts. Beyond the demarcation of transdisciplinary research modes in sustainability science, our empirical analysis revealed three important tensions related to the theory and practice of this research approach: the duality of science and society (and scholars and practitioners); imbalances in the involvement and influence of different societal actor groups; and tensions between societal and academic outputs and impacts.